Tinjauan Sistematis Teori Konstruktivistik: Analisis Prinsip, Implementasi, dan Tantangan dalam Pembelajaran - Mili Sahira Saragih; Neviyarni Neviyarni; Herman Nirwana (Yayasan Cerdas Pedia Indonesia, 2025)
Constructivist learning theory has gained prominence as a foundation for student-centered pedagogy, yet its classroom implementation remains inconsistent. This systematic review analyzes epistemological and pedagogical principles of constructivism, models of instructional implementation, and multidimensional challenges that hinder consistent practice. Empirical and conceptual studies were identified from reputable academic databases using adapted PICO criteria; study quality and risk of bias were assessed with standardized critical appraisal tools, and findings were synthesized thematically. The review confirms strong evidence for constructivist approaches in enhancing engagement, higher-order thinking, and meaningful learning outcomes across diverse contexts. However, implementation is constrained by structural misalignment between curricula and assessment regimes, institutional and cultural resistance, and teachers’ struggles with five interrelated dilemmas concerning conceptions, design, classroom management, assessment, and accountability. The study concludes that realizing the full potential of constructivism requires coherent, system-level integration of curriculum, assessment, and sustained professional development for teachers.